Practicing biology a student workbook - Heitz, Jean; Giffen, Cynthia (Pearson Eduction, 2008)
This workbook offers a variety of activities to suit different learning styles. Activities such as modeling and mapping allow students to visualize and understand biological processes. New activities focus on reading and developing graphs and basic skills.--Provided by publisher.